2022
DOI: 10.3389/fphar.2022.911704
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide-Induced Vasodilation: The Involvement of Vascular Potassium Channels

Abstract: Hydrogen sulfide (H2S) has been highlighted as an important gasotransmitter in mammals. A growing number of studies have indicated that H2S plays a key role in the pathophysiology of vascular diseases and physiological vascular homeostasis. Alteration in H2S biogenesis has been reported in a variety of vascular diseases and H2S supplementation exerts effects of vasodilation. Accumulating evidence has shown vascular potassium channels activation is involved in H2S-induced vasodilation. This review aimed to summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…While it is tempting to regard plasma sulfides exclusively as toxic species based on this and our previous report [ 93 ], sulfides have also been shown to be protective in vascular disease [ 78 ], where free sulfide preserves brain vasomotion [ 80 ], protects against global and focal cerebral ischemic injury [ 81 , 82 ] and is involved in blood brain barrier integrity [ 83 , 84 ]. Thus, it is highly likely that some sulfide species are neuro-protective, and that elevated hydrogen sulfide with limited generation of acid-labile and bound sulfides is adaptive, but that accumulation of bound (and possibly acid labile) sulfides become cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is tempting to regard plasma sulfides exclusively as toxic species based on this and our previous report [ 93 ], sulfides have also been shown to be protective in vascular disease [ 78 ], where free sulfide preserves brain vasomotion [ 80 ], protects against global and focal cerebral ischemic injury [ 81 , 82 ] and is involved in blood brain barrier integrity [ 83 , 84 ]. Thus, it is highly likely that some sulfide species are neuro-protective, and that elevated hydrogen sulfide with limited generation of acid-labile and bound sulfides is adaptive, but that accumulation of bound (and possibly acid labile) sulfides become cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfides are protective in vascular disease [ 78 ], with decreased levels of bound, acid labile and total sulfides predicting cardiovascular disease risk [ 79 ]. Studies have demonstrated that hydrogen sulfide is produced by cerebral microvessels; we and others have also previously described that free sulfide preserves brain vasomotion [ 80 ], protects against global and focal cerebral ischemic injury [ 81 , 82 ], and participates in blood brain barrier integrity [ 83 , 84 ].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired mitochondrial function occurs as hydrogen sulfide exerts toxic effects on cytochrome c oxidase, an enzyme in mitochondrial aerobic metabolism 13 . Vascular smooth muscle relaxation occurs as a result of activation of adenosine triphosphate–sensitive potassium channels and inhibition of angiotensin‐converting enzyme at the vascular endothelium 13,14 . The effect of hydroxocobalamin on hydrogen sulfide action is less clear than with NO, but it is proposed that hydroxocobalamin may scavenge circulating hydrogen sulfide as seen in animal models of hydrogen sulfide toxicity 15 …”
Section: Introductionmentioning
confidence: 99%
“…13 Vascular smooth muscle relaxation occurs as a result of activation of adenosine triphosphate-sensitive potassium channels and inhibition of angiotensin-converting enzyme at the vascular endothelium. 13,14 The effect of hydroxocobalamin on hydrogen sulfide action is less clear than with NO, but it is proposed that hydroxocobalamin may scavenge circulating hydrogen sulfide as seen in animal models of hydrogen sulfide toxicity. 15 Hydroxocobalamin is one of several vitamers of vitamin B 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that H 2 S plays a crucial role in regulating various aspects of cardiovascular health, including blood pressure, vascular tone, inflammation, and oxidative stress [29]. H 2 S has been shown to promote vasodilation by activating potassium channels and inhibiting calcium channels in vascular smooth muscle cells [30]. Moreover, H 2 S has been found to regulate endothelial function by stimulating the release of nitric oxide (NO), a potent vasodilator that plays a key role in maintaining vascular homeostasis.…”
Section: Introductionmentioning
confidence: 99%